THE MEGARA AND ATHENS SOPHISM: : SYNTAX IS NOT ENOUGH (Polymatheia - Revista de Filosofia, 2021)
In this paper, a sophism attributed to Chrysippus of Soli by Diogenes Laërtius is reviewed. To do that, the general framework of the mental models theory is assumed, and the conclusion is that the sophism is a problem only if just its logical form is considered. If the semantic and pragmatic aspects involved in it are also taken into account, the difficulties disappear and it can be easily understood why people tend to reject the conclusion of sophisms such as the aforementioned one. In this way, another point in which the paper insists is that, probably, syntax and logical form are not the main elements in reasoning and language.